How do Planktonic Particle Collection Methods Affect Bacterial Diversity Estimates and Community Composition in Oligo-, Meso- and Eutrophic Lakes? - Xie, Guijuan; Tang, Xiangming; Gong, Yi; Shao, Keqiang; Gao, Guang (Frontiers in Microbiology, 2020)
Particles are hotspots of bacterial growth and nutrient recycling in aquatic ecosystems. In the study of particle-attached (PA) and/or free-living (FL) microbial assemblages, the first step is to separate particles from their surrounding water columns. Widely used collection techniques are filtration using different pore size filters, and centrifugation; however, it is unclear how the bacterial diversity, bacterial community structure (BCS) and taxonomic composition of PA assemblages are affected by different particle collection methods. To address this knowledge gap, we collected particles from eutrophic Lake Taihu, mesotrophic Lake Tianmu and oligotrophic Lake Fuxian in China, using filtration with five pore size of filters (20 μm, 10 μm, 8.0 μm, 5.0 μm and 3.0 μm), and centrifugation. Bacterial communities were then analyzed using Illumina MiSeq sequencing of the 16S rRNA gene. We found that PA collection method affected BCS significantly in all lakes. Centrifugation yielded the highest species diversity and lowest mean percentage of photoautotrophic Cyanobacteria in Lake Taihu, but not in the other two lakes, thus highlighting the potential compatibility of this method in the study of PA assemblage in eutrophic lakes. The high bacterial diversity and low relative percentage of Cyanobacteria was in samples retained on 5.0 μm filters in all lakes. These results suggest that collecting PA samples in lakes using filters with 5.0 μm pore size is the preferred protocol, if species diversity and heterotrophic bacteria are the top research priorities, when comparing bacterial communities in different trophic lakes at the same time. The present study offers the possibility of collecting PA samples using unified methods in oligotrophic to eutrophic lakes.